Teachers as health promoters: a longitudinal study of the effect of a health education curriculum for trainee teachers on their practice in schools. (13th November 2015) - Pickett, Karen; Byrne, Jenny; Rietdijk, Willeke; Shepherd, Jonathan; Roderick, Paul; Grace, Marcus
Abstract: Background: Teachers have an important role as health promoters; therefore they require adequate training to meet this responsibility. However, little is known about how pre-service health education training affects teachers' knowledge and attitudes towards promoting health in school once they are qualified. Our research assessed recently qualified teachers' attitudes towards, experiences of, and perceived confidence and skills for health promotion, up to 3 years after an innovative health curriculum developed at the University of Southampton for pre-service teachers. Methods: We sent an online and postal 15 min questionnaire to all contactable teachers (n=976) who had qualified at Southampton Education School between 2012 and 2014. It assessed their self-reported attitudes towards promoting health, experiences of and perceived competence and confidence to promote health, and perceptions of their school's health promotion culture and environment. The curriculum consisted of a Health Day with workshops and subsequent school-based tasks, delivered via a multiagency approach. Results are reported as the percentage of all people who responded to a particular question. Findings: The response rate was 11% (n=104). Positive attitudes towards promoting health were reported by 88 (96·7%) of 91 teachers. 50 (74·6%) of 67 teachers felt that the training had positively influenced their health education teaching. Between 57·3% (55/96) and 87·5% (84/96) felt confident and skilled in teaching ten health-related topics (median 71·9%). The teachers most frequently reported that their life experience (87/95, 91·6%), practical teaching experience (75/94, 79·8%), and support received in school since qualifying (65/93, 69·9%) had been influential in their gaining competence. However, 80 (81·6%) of 98 teachers agreed with the statement that "academic attainment is prioritised over other elements of pupils' education" in their school. Interpretation: The low response rate creates possible participation bias and generalisability issues. However, the high proportions of these teachers reporting positive attitudes towards and feeling confident and competent in promoting health suggest a possible longer term positive effect of the training. The findings indicate that teachers value support from colleagues, and practical and life experience for developing competence, but feel that health education is not always prioritised. The Southampton training model could be used by other initial teacher education institutions. Our findings do not indicate, however, how such training could ultimately affect pupils' health and education outcomes. Funding: The Leverhulme Trust.